MEASUREMENT OF TECHNOWARE AND HUMANWARE READINESS IN ORDER TO MEET SNI 07-2052-2002 (REINFORCED BAR) IN PT JAKARTA CAKRATUNGGAL STEEL MILLS - TANIA NIM 13414087, VIOLLA
PT Jakarta Cakratunggal Steel Mills (PT JCSM) is one of the producers of reinforced steel bar in Indonesia. Currently, PT JCSM is facing continuous defect problem of billet with different type of defects in every one or two weeks period. This is due to the lsack of adequate production facilities and equipment. In addition, there is also a problem with the production reporting culture. This is due to the target for billet defects was not achieved. Therefore, this research aimed to measured gaps between the actual level sophistication and the standard level sophistication of technoware (machine and equipment) and humanware (operator). Based on the method of measuring the level of sophistcation for technoware and humanware that adopts the QFD methodology, there are three main stages. The first stage is measuring the level of sophistication for SNI requirements. At this stage, the product output standard is defined as customer needs and benefits and the production process is defined as technical response. Then, an assesssment of the relationship between customer needs and benefits and production process is made by expert judgement. The next stage is a step to measure the level of sophistication in industry. The third stage is the measurement of technoware and humanware readiness of industry in meeting SNI requirements by calculating planning matrix and technical matrix. Planning matrix consists of seven variables measuring fulfillment effort of technoware and humanware towards product standards. Technical matrix consisting of six variables that show the effectiveness of the performance of the production process in the effort to meet the target quality requirements. Based on the measurement result of technical matrix, it is known that for technoware component there are nine production processes that do not meet the standard. Futhermore, gap analysis, contribution and pareto analysis are used to determine the priority of production process improvement that will be focused, namely tempcore process, alloying process, sample and temperature inspection with cumulative contribution up to 69.9%. Based on the priority of production process improvement, the proposed solution is to create a best practice recording file for tempcore process and alloying process and investment in SSC liquid sampler for sampling and temperature inspection process. As for the humanware components there are two production processes that do not meet the standards that is samples and temperature inspection and billet cutting process. The proposed solution is to conduct operator training on sampling and temperature inspection and billet cutting process.